The Relevant Physical Trace in Criminal Investigation - Durdica Hazard (Wolters Kluwer Medknow Publications, 2016)
A criminal investigation requires the forensic scientist to search and to interpret vestiges of a criminal act that happened in the past. The forensic scientist is one of the many stakeholders who take part in the information quest within the criminal justice system. She reads the investigation scene in search of physical traces that should enable her to tell the story of the offense/crime that allegedly occurred. The challenge for any investigator is to detect and recognize relevant physical traces in order to provide clues for investigation and intelligence purposes, and that will constitute sound and relevant evidence for the court. This article shows how important it is to consider the relevancy of physical traces from the beginning of the investigation and what might influence the evaluation process. The exchange and management of information between the investigation stakeholders are important. Relevancy is a dimension that needs to be understood from the standpoints of law enforcement personnel and forensic scientists with the aim of strengthening investigation and ultimately the overall judicial process.